A luta pela reforma agraria no Brasil: uma análise à luz do pluralismo jurídico comunitário participativo - Vaz, Clarissa Machado de Azevedo (2016)
The present dissertation has as object of analysis the search for agrarian reform practiced by the Movement of the Workers and Landless Rural Workers, and how this search ranks within the paradigm of Legal Pluralism and, in the space of participatory community developed by Antônio Carlos Wolkmer. It sought to demonstrate the foundations of Law, and the advances after its polarization between monism and pluralism, to the current analysis of the relation between monism and pluralism in Brazilian Law. Then, in the second chapter, the analysis was based on the changes in the world economic model that occurred contemporaneously with the elaboration and promulgation of the Land Statute, legislation used as a time frame for discussing the Agrarian Reform in Brazil, and what is the influence of the world economic moment in relation to the distribution of land in Brazil. The third chapter seeks the historical formation of the MST, its form of action and composition and, from this, how its actions can be associated to Legal pluralism, and in particular, to Participative Community Legal Pluralism.